Sharia Insurance Dispute Resolution in Indonesia - Hidayati, Eka; Dr. Mariani, MH (Sharia Journal and Education Center Publishing, 2023)
ABSTRACT Islamic insurance, like conventional insurance, can lead to disputes between policyholders and insurance companies. These disputes can include claim denials, policy ambiguities, and questions about coverage. The resolution of these disputes can be complex due to the sharia aspects that need to be considered. In this study, qualitative research methods are used to understand the rules related to the settlement of sharia insurance disputes in Indonesia. Litigation is usually the last resort in dispute resolution, as it is costly and time-consuming. However, if non-litigation means do not yield satisfactory results, litigation may be necessary to determine the rights and obligations of each party. In the context of Islamic law, the litigation process must comply with sharia principles. Disputes in sharia insurance can be resolved through the Religious Court, but other methods such as deliberation, mediation or arbitration can also be used if agreed in the contract. If the dispute is resolved through negotiation, then no other dispute resolution method is required. However, if there is no agreement, then other sharia insurance dispute resolution mechanisms listed in the policy can be pursued. Keywords : Sharia, insurance, resolution, Indonesia ABSTRAK Asuransi syariah, seperti halnya asuransi konvensional, dapat menimbulkan perselisihan antara pemegang polis dan perusahaan asuransi. Sengketa ini dapat berupa penolakan klaim, ketidakjelasan polis, dan pertanyaan tentang pertanggungan. Penyelesaian sengketa ini dapat menjadi kompleks karena adanya aspek syariah yang perlu dipertimbangkan. Dalam penelitian ini, metode penelitian kualitatif digunakan untuk memahami aturan-aturan yang terkait dengan penyelesaian sengketa asuransi syariah di Indonesia. Litigasi biasanya menjadi pilihan terakhir dalam penyelesaian sengketa, karena membutuhkan biaya dan waktu yang lama. Namun, jika cara-cara non-litigasi tidak membuahkan hasil yang memuaskan, litigasi mungkin diperlukan untuk menentukan hak dan kewajiban masing-masing pihak. Dalam konteks hukum Islam, proses litigasi harus sesuai dengan prinsip-prinsip syariah. Perselisihan dalam asuransi syariah dapat diselesaikan melalui Pengadilan Agama, tetapi metode lain seperti musyawarah, mediasi, atau arbitrase juga dapat digunakan jika disepakati dalam kontrak. Jika sengketa diselesaikan melalui negosiasi, maka tidak diperlukan metode penyelesaian sengketa lainnya. Namun, jika tidak ada kesepakatan, maka mekanisme penyelesaian sengketa asuransi syariah lainnya yang tercantum dalam polis dapat ditempuh. Kata kunci : Syariah, asuransi, resolusi, Indonesia